2017
DOI: 10.3389/fendo.2017.00301
|View full text |Cite
|
Sign up to set email alerts
|

Preconception Prebiotic and Sitagliptin Treatment in Obese Rats Affects Pregnancy Outcomes and Offspring Microbiota, Adiposity, and Glycemia

Abstract: Maternal obesity is associated with increased risk of pregnancy complications and greater risk of obesity in offspring, but studies designed to examine preconception weight loss are limited. The objective of this study was to determine if a combined dietary [oligofructose (OFS)] and pharmacological (sitagliptin) preconception intervention could mitigate poor pregnancy outcomes associated with maternal obesity and improve offspring metabolic health and gut microbiota composition. Diet-induced obese female Sprag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 63 publications
2
12
0
1
Order By: Relevance
“…HFD increased energy intake and body weight gain during pregnancy, whereas sitagliptin intervention significantly reduced energy intake and body weight gain during pregnancy. A previous study also provided evidence that preconception sitagliptin treatment reduced body weight gain during pregnancy in a HFD-induced obese rodent model (Dennison, Eslinger & Reimer, 2017). In addition, we found that sitagliptin intervention improved maternal glucose homeostasis.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…HFD increased energy intake and body weight gain during pregnancy, whereas sitagliptin intervention significantly reduced energy intake and body weight gain during pregnancy. A previous study also provided evidence that preconception sitagliptin treatment reduced body weight gain during pregnancy in a HFD-induced obese rodent model (Dennison, Eslinger & Reimer, 2017). In addition, we found that sitagliptin intervention improved maternal glucose homeostasis.…”
Section: Discussionsupporting
confidence: 79%
“…We found that maternal sitagliptin intervention attenuated glucose metabolism and insulin resistance in male offspring at weaning. However, intervening before pregnancy with sitagliptin did not have a significant effect on glucose metabolism (Dennison, Eslinger & Reimer, 2017). These different results may be due to differences in sitagliptin treatment time and duration.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…treatment moderated glucose intolerance and insulin resistance caused by maternal HF diet exposure. Several studies had drew the similar conclusion about the benefit of inulin (Hallam and Reimer, 2014;Dennison et al, 2017). However, recent one study found that C57BL/6J mice fed a HF diet could be susceptible to liver cancer upon consumption of inulin (Singh et al, 2018).…”
Section: Discussionmentioning
confidence: 91%
“…Unlike the postnatal period, few studies have focused on the effect of inulin treatment in utero on infants. Maternal oligofructose treatment in obese female rats during gestation and lactation reduced offspring blood glucose in 17-week-old rats through the gut microbiota (Dennison et al, 2017). Metabolite production by the gut microbiome may affect epigenetic changes.…”
Section: Discussionmentioning
confidence: 99%